Social Norms and Gender Equality : A Descriptive Analysis for South Asia - Bussolo, Maurizio (World Bank, Washington, DC, 2022)
Despite decades of economic growth, gender inequality in South Asia remains remarkably high. Although not the only one, social norms are a crucial driver of various gender outcomes, including differential economic participation. Using repeated cross-sectional data from nationally representative surveys, this paper explores the long term trends of gender outcomes and social norms (proxied by attitudes towards gender roles) in South Asia. The results corroborate the evidence that there has been almost no progress in gender equality in South Asia over the past half-century. There has been little progress on female labor force participation, marriage age, agency, intimate partner violence, and preference for sons, with education being the only exception. The lack of progress is apparent among all socioeconomic groups, including women who live in urban areas, are educated, and have higher incomes. Gender attitudes also remain unchanged, and in some cases, have become more conservative and have a negative relationship with gender outcomes. Better measurements of social norms and better understanding of how their constraining role can be loosened may be critical for achieving gender equality in the region.